THE ARTISTIC AND GNOSTIC INTERPRETATION OF THE NAFS IN THE WORKS OF AHMAD YASSAWI - Zoyir Yusupovich Yallaqayev (International Journal of Literature and Language Studies, 2026)
This article examines the interpretation of the image of the nafs (the lower self) in Ahmad Yassawi’s hikmats, focusing on its artistic and gnostic (irfānī) dimensions. The study explores the oppressive, unbelieving, polytheistic, and animalistic qualities attributed to the nafs, as well as its representation through various symbolic and metaphorical images, including Satan, vain desire, animals, and other allegorical figures. Furthermore, the article analyzes the role of the nafs in human spiritual life, its influence on spiritual perfection, and the methods of liberation from its domination as reflected in Yassawi’s mystical teachings.